Exploring the Power of Graph Theory in Hadron Theory: From Bound States to Quark Systems - Abu-shady, M. (Indonesian Journal of Combinatorics, 2023)
The article discusses how graph theory has been utilized in hadron theory for high energy interactions in recent years. The paper emphasizes the significance of a visual perspective throughout the discussion and explores how graph theory can aid in creating various systems such as bound state systems. Additionally, the paper delves into how graph theory has been used to develop few-body quark systems and how it can connect with adjacency and incidence matrices in the graph theory by providing examples of how these fundamental principles have been applied to topics ranging from hadronic bound states.